OPTIMASI FORMULA EKSTRAK JAHE MERAH (Zingiber officinale) DENGAN METODE KEMPA LANGSUNG MENGGUNAKAN ANALISIS SIMPLEX LATTICE DESIGN - Hayatus Sa'adah (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
Processing of medicinal plants into the appropriate dosage form can ensure security during use. It is a motivation in making acceptable dosage form which is easy and convenient to use, especially the manufacture of ethanol extract red ginger tablets using a combination of starch 1500 and amprotab.The study begins with the manufacture of dry extract of red ginger. Optimization of making tablets using a combination of starch 1500 and disintegrator with simplex lattice design using three formulas is done by direct compaction method. Further testing on the tablet hardness, friability and disintegration time.The results showed starch 1500 has a greater influence increase hardness and disintegration time of tablets, as well as lowering the fragility of the tablet. While the interaction of starch 1500 and disintegrator has no effect on the physical tablet. The optimum proportion of the combination of starch 1500 and disintegrator meet the physical requirements of tablets with a ratio of 4: 6 with 7.99 kg hardness, the friability of 0.32% and disintegration time of 2.42 minutes